Bank Competition and Firm Growth in the Enlarged European Union - Gábor Pellényi; Tamás Borkó (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
We examine the impact of bank competition and institutional factors on net firm entry in a sample of European manufacturing industries over the 1995-2006 period. Taking into account industry differences in the need for external finance, we find that bank competition helps firm entry. In addition, better institutions - especially legal structure and property rights - also have a positive impact, particularly through a better functioning financial system.
info:eu-repo/grantAgreement/EC/FP7/217266
Keywords: D4; G21; L11; L60; O16; 330; market structure; banks; market entry; manufacturing; financial development